Program of activities on social and emotional adaptability for workplace trainees with mental retardation at selected special education schools - Santos, Maria Elena Pabalan (Animo Repository, 2004)
The present investigation aimed to evolve program of activities that will help address the perceived needed social and emotional skills particularly related to Independent living, Career Education and Work Experiences and Off Campus work experience as viewed by the parents, SPED teachers, SPED Administrators, workplace supervisors and the workplace trainees themselves. In order to achieve the objectives of the study, the descriptive developmental method was utilized for the research. The respondents respective views regarding the social and emotional adaptability of the workplace trainees on selected schools were taken and the three highest perceived skills from each component that need to be developed were taken as the major focus of the program created. A total of 120 participants which consisted of 45 parents, 17 SPED teachers, 6 SPED administrators, 5 workplace supervisors and 47 workplace trainees participated. Seventy five respondents came from the 2 public schools and 45 respondents came from the Private schools. To gather the pertinent data, a questionnaire was prepared by the researcher which consisted of 2 parts. Part I gathered personal information about the respondents and Part II focused on their perceptions on the social and emotional adaptability of the workplace trainees of the responding schools. The study went through several stages in order to come up with a sound program such as gathering of the relevant literature, preparation of the questionnaire and its face and content validation, administration of the questionnaire and retrieval and analysis of the data. vi In analyzing and interpreting the results obtained, descriptive statistics such as frequency distribution, percentages and mean were employed. Findings presented the top nine skills that were perceived to have the highest needs to be developed and are shown in the tables in the succeeding chapters. Aside from the top skills, other implications were also discovered such as: Since the friendships of persons with mental retardation tend to be shorter and less stable than those of the non-disabled peers, school facilities need to create opportunities for friendships to form. Workplace trainees need to be taught specific skills for meeting people and of forming friendships. Workplace trainees need to develop social sensitivities that normally evolve in day to day activities. Their environment as well needs to be aware of the differences in the trainees natural reactions to a given social situation. Workplace trainees generally lack the ability to perceive a social situation from another persons point of view, be it co-worker, supervisor, teacher or even their parents.